2005
DOI: 10.1021/ie0506365
|View full text |Cite
|
Sign up to set email alerts
|

New Apparatus for Low-Temperature Investigations:  Measurements of the Multiphase Equilibrium of Mixtures Containing Methane, Ethane, Propane, Butane, Methanol, and Carbon Dioxide

Abstract: A new experimental apparatus has been developed to measure vapor− liquid equilibria (VLE) and vapor−liquid−liquid equilibria (VLLE) for multicomponent systems containing light hydrocarbons, carbon dioxide, methanol, and water at low temperatures. These systems are particularly difficult to investigate experimentally because of the polarity contrast existing between the polar and nonpolar components. In such systems, the phase equilibrium leads to a heterogeneous distribution of the different components into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Typically, such equipment is specialised to the study of a particular type of phase equilibrium, although greater flexibility is obtained when compositional analysis is coupled with visual observation of phase transitions [10]. The priority for developing the present apparatus was to make the system as flexible as possible and, in particular, suitable for: (a) visual observation of phase behaviour; (b) compositional analysis of equilibrium phases; and (c) in situ measurement of phase properties.…”
Section: Apparatusmentioning
confidence: 99%
“…Typically, such equipment is specialised to the study of a particular type of phase equilibrium, although greater flexibility is obtained when compositional analysis is coupled with visual observation of phase transitions [10]. The priority for developing the present apparatus was to make the system as flexible as possible and, in particular, suitable for: (a) visual observation of phase behaviour; (b) compositional analysis of equilibrium phases; and (c) in situ measurement of phase properties.…”
Section: Apparatusmentioning
confidence: 99%
“…The experimental apparatus (Ruffine et al) used to measure the hydrate formation conditions in the absence of a liquid water phase is shown in Figure . It consists of: A thermostatic air bath containing a sapphire equilibrium cell with a volume of 100 cm 3 .…”
Section: Experimental Studymentioning
confidence: 99%
“…Xia et al[145] measured the solubility of CO 2 in aqueous solutions of methanol and observed that the CO 2 solubility was higher for methanol rich solutions than for water rich solutions. Ruffine et al[146] measured the phase equilibria for systems comprising methane, ethane, propane, butane, CO 2 , and methanol at temperatures as low as about 193 K.Folas et al[147] used a high pressure equilibrium cell to measure the methane solubility in MEG and binary solutions of water + MEG. They showed that for such associating systems, the cubic plus association (CPA) equation of state provides better prediction than the SRK equation of state.…”
mentioning
confidence: 99%